A secretory phospholipase A2 of a fungal pathogen contributes to lipid droplet homeostasis, assimilation of insect‐derived lipids, and repression of host immune responses. (5th April 2022) - Deng, Juan; Lu, Zhuoyue; Wang, Huifang; Li, Ning; Song, Guimei; Zhu, Qiankuan; Sun, Jingxin; Zhang, Yongjun
Abstract: Secretory phospholipase A2s (sPLA2s) are found in a wide range of organisms from bacteria to higher plants and animals and are involved in varied and cellular processes. However, roles of these enzymes in microbial pathogens remain unclear. Here, an sPLA2 (BbPLA2) was characterized in the filamentous insect pathogenic fungus, Beauveria bassiana . BbPLA2 was exclusively expressed in insect hemolymph‐derived cells (hyphal bodies), and its expression was induced by insect‐derived nutrients and lipids, and nutrient starvation. High levels of secretion of BbPLA2 were observed as well as its distribution in hyphal body lipid drops (LDs). Overexpression of BbPLA2 increased the ability of B. bassiana to utilize insect‐derived nutrients and lipids, and promoted LD accumulation, indicating functions for BbPLA2 in mediating LD homeostasis and assimilation of insect‐derived lipids. Strains overexpressing BbPLA2 showed moderately increased virulence, including more efficient penetration of the insect cuticle and evasion of host immune responses as compared to the wild type strain. In addition, B. bassiana ‐activated host immune genes were downregulated in the BbPLA2 overexpression strain, but upregulated by infections with a ΔBbPLA2 strain. These data demonstrate that BbPLA2 contributes to LD homeostasis, assimilation of insect‐derived lipids, and repression of host immune responses. Graphical Abstract: A secretory phospholipase A2, BbPLA2, in a filamentous insect pathogenic fungus, Beauveria bassiana, plays multiple roles in the fungal pathogen and host insect interaction. BbPLA2 either maintains lipid drop homeostasis or participates in assimilation insect‐derived lipids and repression of immune response, and impact fungal virulence against insects as a result.